A Randomized Clinical Trial Evaluating rh-FGF-2/β-TCP in Periodontal Defects. (May 2016) - Cochran, D.L.; Oh, T.-J.; Mills, M.P.; Clem, D.S.; McClain, P.K.; Schallhorn, R.A.; McGuire, M.K.; Scheyer, E.T.; Giannobile, W.V.; Reddy, M.S.; Abou-Arraj, R.V.; Vassilopoulos, P.J.; et al.
Biological mediators have been used to enhance periodontal regeneration. The aim of this prospective randomized controlled study was to evaluate the safety and effectiveness of 3 doses of fibroblast growth factor 2 (FGF-2) when combined with a β-tricalcium phosphate (β-TCP) scaffold carrier placed in vertical infrabony periodontal defects in adult patients. In this double-blinded, dose-verification, externally monitored clinical study, 88 patients who required surgical intervention to treat a qualifying infrabony periodontal defect were randomized to 1 of 4 treatment groups—β-TCP alone (control) and 0.1% recombinant human FGF-2 (rh-FGF-2), 0.3% rh-FGF-2, and 0.4% rh-FGF-2 with β-TCP—following scaling and root planing of the tooth prior to a surgical appointment. Flap surgery was performed with EDTA conditioning of the root prior to device implantation. There were no statistically significant differences in patient demographics and baseline characteristics among the 4 treatment groups. When a composite outcome of gain in clinical attachment of 1.5 mm was used with a linear bone growth of 2.5 mm, a dose response pattern detected a plateau in the 0.3% and 0.4% rh-FGF-2/β-TCP groups with significant improvements over control and 0.1% rh-FGF-2/β-TCP groups. The success rate at 6 mo was 71% in the 2 higher-concentration groups, as compared with 45% in the control and lowest treatment groups. Percentage bone fill in the 2 higher-concentration groups was 75% and 71%, compared with 63% and 61% in the control and lowest treatment group. No increases in specific antibody to rh-FGF-2 were detected, and no serious adverse events related to the products were reported. The results from this multicenter trial demonstrated that the treatment of infrabony vertical periodontal defects can be enhanced with the addition of rh-FGF-2/β-TCP (ClinicalTrials.gov NCT01728844).